A novel method for histopathological analysis of oral squamous cell carcinoma: a pilot study using three-dimensional imaging to enhance local control - Michcik, Adam; Pęksa, Rafał; Garbacewicz, Łukasz; Polcyn, Adam; Choma, Piotr; Wojciechowska, Barbara; Drogoszewska, Barbara (Frontiers in Oncology, 2025)
One factor that enhances the survival of patients with oral squamous cell carcinoma (OSCC) is improved local control. Many prognostic factors (PF) influence a patient’s prognosis, one of which is the correct histopathological excision margins. Standard histopathological analysis does not allow for the precise determination of the locations of individual hematoxylin and eosin (H&E) slides, which is clinically very important. In extensive tumors, the ability to precisely identify the sites with the narrowest microscopic excision is essential for accurately interpreting postoperative results and making proper clinical decisions. Therefore, a protocol has been developed to precisely localize individual H&E-stained tissue slides on virtual three-dimensional (3D) OSCC images. This approach provides a virtual map of the entire excised tumor, allowing accurate identification of areas with the narrowest histopathological margins (HM). As a result, if reoperation is necessary, it is possible to precisely determine where to widen the OSCC excision or plan adjuvant radiotherapy with greater accuracy. The proposed pilot study is based on the virtual three-dimensional OSCC model of the floor of the mouth cancer. Using 3D scanning technology, a user-friendly protocol has been created.